1984
DOI: 10.1111/j.1476-5381.1984.tb16533.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adenosine, adenosine triphosphate and structural analogues on glucagon secretion from the perfused pancreas of rat in vitro

Abstract: 1 The effects of adenosine, adenosine triphosphate (ATP) and structural analogues have been studied on glucagon secretion from the isolated perfused pancreas of the rat in the presence of glucose (2.8 mM). 2 Adenosine induced a transient increase of glucagon secretion. This effect was concentrationdependent in the range of 0.165 to 165 jiM. ATP also induced an increase, but the effect was no greater at 165 jiM than at 16.5 jiM. 3 2-Chloroadenosine, an analogue more resistant to metabolism or uptake systems tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…The activation of these receptors induced a transient increase of glucagon secretion. We have also shown that ATP was effective after hydrolysis to adenosine (Chapal et al, 1984). It is now generally accepted that there are two subtypes of extracellular receptors involved in the action of adenosine.…”
Section: Introductionmentioning
confidence: 72%
“…The activation of these receptors induced a transient increase of glucagon secretion. We have also shown that ATP was effective after hydrolysis to adenosine (Chapal et al, 1984). It is now generally accepted that there are two subtypes of extracellular receptors involved in the action of adenosine.…”
Section: Introductionmentioning
confidence: 72%
“…Consequently, not only ATP and ADP but also their more stable /a/p-methylene analogues induced mobilization, whereas AMP, adenosine and P/y-methylene ATP were without obvious effects. Measurements of the release ofinsulin and glucagon from the perfused rat pancreas have provided evidence for the existence of P,-purinoceptors in the a2-cells and P2-receptors in the P-cells (Loubatieres-Mariani et al, 1979;Chapal & Loubatieres-Mariani, 1981;Chapal et al, 1984). It should be emphasized that pancreatic islets from obh ob-mice are practically devoid of the glucagonproducing a2-cells (Hellman, 1965).…”
Section: Discussionmentioning
confidence: 99%
“…NECA, induced dose-dependent glucagon release from α cells, presumably via A 2 receptors [39,41,42]. These actions were eliminated by aminophylline and theophylline.…”
Section: Endocrine Pancreas β Cellsmentioning
confidence: 91%